The Association between Metabolic Syndrome and Elevated Alanine Aminotransferase Levels in an Indigenous Population in Northern Taiwan: A Community-Based and Cross-Sectional Study. (9th December 2020) - Chen, Yi-Fang; Lin, Yen-An; Yeh, Wei-Chung; Tsao, Yu-Chung; Li, Wen-Cheng; Fang, Wei-Ching; Chen, I-Ju; Chen, Jau-Yuan
Abstract : Our study aims to determine the prevalence of metabolic syndrome (MetS) among the Northern Taiwanese indigenous population and to explore the relationship between MetS and liver enzyme, especially serum alanine transaminase (ALT). This is an observational and cross-sectional study that was conducted in remote villages of an indigenous community in Northern Taiwan between 2010 and 2015. MetS was defined based on the revised NCEP/ATPIII criteria from Taiwan Health Promotion Administration. A total of 454 participants were included in the analysis. There were 277 people with MetS and 177 people without. The prevalence of MetS was 61.01%. The average age was 49.50 years. People with MetS had a significantly higher liver enzyme (ALT) level than those without MetS. In addition, the study showed that participants with higher ALT had a tendency towards a higher prevalence of MetS (76.7% vs. 57.3%, p  = 0.001). The adjusted odds ratio (OR) of ALT levels >36 U/L for MetS was 2.79 (95% CI = 1.24–6.27, p  = 0.01). The area under the ROC curve (AUC) of the ALT level was 0.63 (95% CI = 0.58–0.68, p  < 0.001), which showed that the ALT level was positively associated with MetS. The overall prevalence of MetS was 61.01% in the highland indigenous population in Northern Taiwan; this study indicated that higher serum ALT levels were associated with an increased risk of MetS.